REKONSTRUKSI KEDUDUKAN DPD DAN DPR MENUJU BIKAMERAL YANG SETARA - Sulardi, Sulardi (Jurnal Media Hukum, 2012)
As a state institution that was born from the amendment of the Constitution 1945, Regional Representative Council (hereafter: Council) has authority and supervision functions of such legislation in general. There are two important issues related to the council. First, the Council has the authority and supervision functions which are stated in constitution. Second, the Council has an equal position with the Parliament. By looking at the role of the Council and the Parliament stated in constitution, it can be seen that the Council is merely a complimentary institution. On the other hand, the institution which has the real legislation, supervision and budgeting functions is the Parliament. The provision contained in the constitution indicates inequality and imbalance between the Council and the Parliament, it does not mean that the Council has no role in the process of state. The Council should continue to run its legislation, supervision and budgeting functions optimally. Futhermore the Council should establish optimal relation with local communities. In this case, the Council is more flexible since its presence does not represent any political parties. Therefore the Council may have âpublic hearingâ with various groups in society.